Assessment of Nutritional Status Using SGA (Subjective Global Assessment) and MIS (Malnutrition Inflammation Score) Tools in Hemodialysis Patients - Lestari, Pina; Rustandi, Budi; Istianah, Istianah; Pahlawan, Rizky Gumilang (Universitas Airlangga, 2023)
Introduction: One of the problems often found in patients undergoing hemodialysis is changes in their nutritional status. Patients with hemodialysis who are malnourished have a higher risk of disease and death. This nutritional disorder can be overcome by assessing nutritional status. Apart from using the SGA (Subjective Global Assessment) method, the MIS (Malnutrition Inflammation Score) method can also be used. The aim of this study was to compare differences in nutritional status of patients on hemodialysis using the SGA and MIS instruments. Methods: This research was a quantitative research with a cross-sectional design. The research sample consisted of 75 patient with hemodialysis at one of military hospital, who were selected using non-probability techniques with a total sampling approach. The statistical test used is the Mann-Whitney test with level of significance 0.05 to compare differences between variables. Results: Using the SGA tool, it was found that more than half of respondents (66.7%) were in the moderate nutrition category, while only 9.3% were in the malnutrition category. In contrast, with MIS tools, it was found that 34.7% were in the mild malnutrition and not malnourished category, while 65.3% were in the moderate to severe malnutrition category. Furthermore, statistical analysis shows that there is a significant difference (p = 0.001) between the use of SGA and MIS in assessing nutritional status in patients with hemodialysis. Conclusion: It can be concluded that there is a difference between the use of SGA and MIS in assessing nutritional status in patients with hemodialysis. Further research, could explore more for the advantages and disadvantages of each instrument, including the level of accuracy and sensitivity.